Automated Intelligence: Enhancing Environmental Protection with AI and Electrical Systems - AHMED ATIYAH ITWAYYA; MOHSIN N. AL-MALIKI; HASANAIN A. H. AL- BEHADILI (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The global community is increasingly focusing on conservation. To combat pollution andresource wastage, modern technologies, like automation and AI are widely employed in environmentalprotection tools. This study delves into the utilization and advancement of automation and AI inenvironmental protection tools examining their real world applications across sectors like wastewatertreatment, air pollution control, solid waste management, metallurgy and energy supervision. Furthermoreit investigates the fusion of automation and artificial intelligence in the development of environmentalprotection tools. The study also addresses aspects such as data collection, performance monitoring,sustainable growth, prevailing challenges and future trends. Through an analysis it underscores thepotential of automation and artificial intelligence in enhancing environmental protection tools effectivenesstowards achieving sustainable conservation goals. Lastly recommendations for research are proposed todrive innovation and enhancement of environmental protection technology. This study aims to offerinsights and guidance for both research endeavors and practical applications, within the realm ofenvironmental protection technology.